Effectiveness in Handling People with Mental Disorders - Usman, Usman; Ibrahim , Akmal; Hasniati, Hasniati; Abdullah, Tang (Journal La Bisecoman, 2025)
The research addresses how well North Kalimantan Province of Indonesia executes mental health policies to deal with mental disorders (ODGJ) among its population. The practical implementation of Law No. 18 of 2014 faces substantial hurdles because the law specifies integrated service delivery with promotive and curative approaches while preventive and rehabilitative approaches. The study adopted qualitative methods to gather data by interviewing stakeholders along with analyzing documents and performing field observations. The analysis through thematic methodology revealed five significant obstacles which include insufficient infrastructure, poor inter-agency cross-sectoral coordination along with continuous financial limitations and inexperienced workforce shortage and the failure to maximize community health services. Multiple actors take part in implementing the system yet it remains ineffective because policy and execution operate apart from each other structurally. Research results demonstrate an immediate necessity for mental health infrastructure funding alongside improved governance systems and budget inclusion policies as well as human resource development and official recognition of community-led mental health care designs. Through this study researchers gain essential knowledge about strengthening mental health policy in resource-limited settings for providing sustainable and inclusive care to ODGJ patients.